Time-resolved characteristics of a nanosecond pulsed multi-hollow needle plate packed bed dielectric barrier discharge - QIN, Liang; LI, Yao; GUO, Hao; JIANG, Nan; SONG, Ying; JIA, Rui; ZHOU, Xiongfeng; YUAN, Hao; YANG, Dezheng (Plasma science & technology, 2024)
In this paper, self-designed multi-hollow needle electrodes are used as a high-voltage electrode in a packed bed dielectric barrier discharge reactor to facilitate fast gas flow through the active discharge area and achieve large-volume stable discharge. The dynamic characteristics of the plasma, the generated active species, and the energy transfer mechanisms in both positive discharge (PD) and negative discharge (ND) are investigated by using fast-exposure intensified charge coupled device (ICCD) images and time-resolved optical emission spectra. The experimental results show that the discharge intensity, number of discharge channels, and discharge volume are obviously enhanced when the multi-needle electrode is replaced by a multi-hollow needle electrode. During a single voltage pulse period, PD mainly develops in a streamer mode, which results in a stronger discharge current, luminous intensity, and E / N compared with the diffuse mode observed in ND. In PD, as the gap between dielectric beads changes from 0 to 250 μm, the discharge between the dielectric bead gap changes from a partial discharge to a standing filamentary micro-discharge, which allows the plasma to leave the local area and is conducive to the propagation of surface streamers. In ND, the discharge only appears as a diffusion-like mode between the gap of dielectric beads, regardless of whether there is a discharge gap. Moreover, the generation of excited states and is mainly observed in PD, which is attributed to the higher E / N in PD than that in ND. However, the generation of the radical in ND is higher than in PD. It is not directly dominated by E / N , but mainly by the resonant energy transfer process between metastable and . Furthermore, both PD and ND demonstrate obvious energy relaxation processes of electron-to-vibration and vibration-to-vibration, and no vibration-to-rotation energy relaxation process is observed.